Respon Imun Itik Bali terhadap Berbagai Dosis Vaksin Avian Influenza H5N1 - Kade Suardana, Ida Bagus; Ritha Krisna Dewi, Ni Made; Kade Mahardika, I Gusti Ngurah (Jurnal Veteriner; Vol 10 No 3 (2009))
A study was carried out to investigate the immune response of Bali ducks against various doses ofAvian Influenza H5N1 vaccine. The study was carried out using a complete Random-Split in Time researchdesign as many as 40 of Bali ducks of 3 months age were kept separately in 4 groups. The ducks werevaccinated twice in two week interval with AI H5N1 vaccine of 0 (as negative control), 1/2, 1, and 2 doses.Sera were collected one day before first vaccination, then every week until three weeks after the secondvaccination. All sera were tested by hemaglutination inhibition (HI) test. The result shows that antibodylevel with double dose was significantly higher than single dose, half dose, and negative control (P<0.01).However antibody level in ducks vaccinated with single and half dose did not show any significant difference(P > 0.05).
Keywords: Bali duck, AI H5N1 Vaccine, antibody HI